Formation of a Vaccinia Virus Structural Polypeptide from a Higher Molecular Weight Precursor: Inhibition by Rifampicin - Katz, Ehud (1970)
A vaccinia virus core polypeptide, with a molecular weight of 76,000 and a relative deficiency in tryptophan, was shown by pulse-chase experiments to form from a precursor. The latter may be a rapidly labeled, 125,000-molecular weight, tryptophan-deficient, virus-induced polypeptide, which diminished in quantity during the chase period and was barely detectable after two to three hours. Rifampicin completely prevented the formation of the core polypeptide without inhibiting the synthesis of the precursor. A rifampicin-resistant vaccinia mutant was used to demonstrate the specificity of this effect. The sequence of events after the removal of the drug suggested that cleavage of the precursor occurs during the formation of the virus core. Rifampicin appears to act by interrupting earlier maturational events which precede the formation of the core polypeptide.